Pengaruh perbedaan waktu inseminasi buatan terhadap keberhasilan kebuntingan sapi Brahman Cross - fakhri alfi annashru; M. Nur Ihsan; Aulia Puspita Anugrah Yekti; Trinil Susilawati (Faculty of Animal Science, Universitas Brawijaya, 2017)
The purpose of this research is to acknowledge the difference of AI time towards Brahman Cross Cow’s pregnancy rate determined by time and Non Return Rate (NRR). The subjects in this research are 75 female Brahman Cross. Methods that were used during this research are fiels testing. Selection method of the sample livestock used is Purpose Sampling with criterias : Female adult cow with weight >250kg, aged 1,5 – 2 years, healthy, and free from any disease, and at least have mating urge. Materials used during this research are frozen cow semen that acquired from Balai Inseminasi Buatan (BIB) Lembang, Bandung, West Java widh 35-40% motility. The variabels are Cow’s pregnancy and mating urge’s symptomps. Data acquired duringthis reserch are analyzed descriptively and chi-square tested. Supportive datas are food and valuefrom heat detector (HD). Research result shows that Brahman Cross species which AI within 0-4 hours interval have higher CR according to NRR1, which is 70%. Compared with the other breed that AI within 8-12 hour interval, which had 37,14% CR value. According to chi-square test, the difference of AI time of Brahman Cross are p<0.05 which means that the difference of AI time of cow is affecting the pregnancy rate. It is advised that AI is executed during 0-4 hour interval after showing mating symptomps and further reviewed about the difference between AI execution time of Brahman Cross and further observation of NRR2 until NRR3 and also Pregnancy Test to know the pregnancy success rate of Brahman Cross.